2000
DOI: 10.1080/08958370050029743
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and Thermoregulatory Toxicity of Residual Oil Fly Ash in Cardiopulmonary-Compromised Rats

Abstract: Recent epidemiological studies have reported a positive association between levels of ambient particulate matter ( PM) and daily morbidity and mortality due to respiratory or cardiovascular causes; however, toxicological evidence supporting these ndings is limited. The present study compared cardiac and thermoregulatory responses to intratracheal instillations of residual oil y ash ( ROFA) in normal and cardiopulmonary-compromised male Sprague-Dawley rats. Animals ( n = 64) were implanted with radiotelemetry t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
(33 reference statements)
2
12
0
Order By: Relevance
“…A possible mechanism, which has gained attention in the last few years, is that particulate matter alters the autonomic control of the heart [3]. Animal studies have shown that exposure to combustion particles can produce a reduction in heart rate variability, which reflects alterations in cardiac autonomic function that are considered a risk factor for sudden death and death from arrhythmia [36][37][38]. These data have been confirmed in humans.…”
Section: Potential Mechanismssupporting
confidence: 63%
“…A possible mechanism, which has gained attention in the last few years, is that particulate matter alters the autonomic control of the heart [3]. Animal studies have shown that exposure to combustion particles can produce a reduction in heart rate variability, which reflects alterations in cardiac autonomic function that are considered a risk factor for sudden death and death from arrhythmia [36][37][38]. These data have been confirmed in humans.…”
Section: Potential Mechanismssupporting
confidence: 63%
“…A similar association has been observed in a controlled exposure study in humans (Gong et al, 2004) and in animals exposed to residual oil fly ash, a component of PM 2.5 (Campen et al, 2000;Watkinson et al, 1998;Wellenius et al, 2002).…”
supporting
confidence: 71%
“…Healthy SD rats instilled with the highest dose (2.5 mg) of ROFA (19) demonstrated an initial 50-bpm decrease in HR, in conjunction with a 2.0°C decrease in T co (Figure 3). These Changes in core temperature in healthy mice exposed to O 3 while maintained at normal ambient temperature.…”
Section: Particulate Matter/metals Instillationmentioning
confidence: 99%
“…Healthy rats exposed via IT procedures to ROFA and other PM demonstrated significant biphasic, dose-related responses consisting of both acute (0-6 hr post-IT) and delayed (12-72 hr post-IT) bradycardia and hypothermia, accompanied by a high incidence of cardiac arrhythmias and substantial pulmonary inflammation (13,14,(17)(18)(19). Healthy SD rats instilled with the highest dose (2.5 mg) of ROFA (19) demonstrated an initial 50-bpm decrease in HR, in conjunction with a 2.0°C decrease in T co (Figure 3).…”
Section: Particulate Matter/metals Instillationmentioning
confidence: 99%